DESIGNING AND IMPLEMENTING AN INTEGRATED THEMATIC TEACHING MODEL BASED ON A SCIENTIFIC APPROACH TO IMPROVEBASIC EDUCATION STUDENTS' LEARNING OUTCOMES - Muhammad Syahrul; Munawir; Nurul Masruni; Rasida Hairanie; Augusta De Jesus Magalhaes (Indonesian Journal of Education (INJOE), 2023)
This research endeavors to reshape the educational landscape by introducing an innovative pedagogical paradigm—integrating thematic teaching grounded in the scientific approach. This study meticulously designs, implements and assesses a holistic educational model to elevate primary education students' learning outcomes. The study delves into the core tenets of integrated learning, capitalizing on the interconnectedness of knowledge. Students are exposed to a dynamic educational experience that transcends traditional subject boundaries by seamlessly weaving diverse subjects into thematic units. The scientific approach serves as the bedrock of this model, fostering inquiry-based learning, critical thinking, and evidence-based reasoning. Employing a mixed-methods approach, the research combines quantitative assessment tools with qualitative insights, offering a comprehensive understanding of the model's impact. Preliminary findings significantly increase post-assessment scores, affirming the model's efficacy in enhancing subject mastery and cognitive growth. Moreover, qualitative data underscore heightened engagement, collaborative problem- solving, and enthusiasm for learning. The implications of this research resonate beyond the classroom, echoing the call for transformative pedagogical methodologies in a rapidly evolving world. This study bridges the chasm between theoretical constructs and tangible outcomes, advocating for a pedagogical shift that equips students with the skills to navigate complex challenges. As education stands on the precipice of reform, this research is a testament to the potential of integrated thematic teaching to catalyze holistic learning experiences